In silico identification and in vivo validation of a set of evolutionary conserved plant root-specific cis-regulatory elements - Christ, Aurélie; Mägele, Ira; Ha, Nati; Maizel, Alexis (Mechanisms of development, 2012)
Marker genes are specifically expressed in a tissue, organ or time of development. Here we used a computational screen to identify marker genes of the root in Arabidopsis thaliana. We mined the existing transcriptome datasets for genes having high expression in roots while being low in all other organs under a wide range of growth conditions. We show that the root-specificity of these genes is conserved in the sister species Arabidopsis lyrata, indicating that their expression pattern is under selective pressure. We delineated the cis-regulatory elements responsible for root-specific expression and validated two third of those in planta as bona fide root-specific regulatory sequences. We identified three motifs over-represented in these sequences, which mutation resulted in alteration of root-specific expression, demonstrating that these motifs are functionally relevant. In addition, the three motifs are also over-represented in the cis-regulatory regions of the A. lyrata orthologs of our root-specific genes, and this despite an overall low degree of sequence conservation of these regions. Our results provide a resource to assess root-identity in the model genus Arabidopsis and shed light on the evolutionary history of gene regulation in plants.